Proyecto de prefactibilidad para la creación de una microempresa productora y comercializadora de papas con pollo fritas bajas en calorías en la ciudad de Loja. - Torres Veintimilla, Johanna Lisseth (2023)
The present research work called "Pre-feasibility project for the creation of a micro enterprise producing and marketing low calorie fried potatoes with chicken in Loja city", established as general objective to develop a project to determine the pre-feasibility of the creation of a micro enterprise producing and marketing low calorie fried potatoes with chicken in the city of Loja; the following methods were used: deductive, inductive, descriptive and explanatory, it had a quantitative and qualitative approach, the type of research was exploratory and descriptive; the use of data collection techniques such as: observation, survey, population and sample where it was possible to segment the population of the city of Loja allowing to have a population of 63816 inhabitants achieving a sample of 397 inhabitants. With the information from the surveys, it was found that in the city of Loja there is an unsatisfied demand of 1348992 units of potatoes; we proceeded to determine the location, which was in the parish of San Sebastian; the project has an installed production capacity of 196 units per day and 49196 units per year; the project starts with 80% of the machinery working, resulting in a daily production of 157 units; the company generates 7 jobs during its life cycle. It was concluded that the project is feasible for 5 years, even though at the beginning it has a low profit of 3.91%, the annual income will vary significantly over the years and it is possible to expand because the unsatisfied demand is high. It is recommended to start with two air fryers in order to acquire customers and if the demand is high increase the machinery to meet the needs with more production.